2022 Methods-of-Payment Survey report: Cash use over 13 years - Christopher Henry; Doina Rusu; Matthew Shimoda (Bank of Canada, 2024)
We present results from the 2022 Methods-of-Payment Survey, including updated payment shares based on a three-day shopping diary. We highlight long-term trends in cash holdings, management and use observed across results from previous surveys in 2009, 2013 and 2017. We also review recent trends relating to the COVID-19 pandemic using data from 2020 and 2021. We assess various factors associated with long-term trends in cash use.
Keywords: D83; E41; 330; Bank notes; Coronavirus disease (COVID-19); Digital currencies and fintech; Financial services